Multiplier Operated Controller for CCM Boost PFC Converter With Regulated Input Impedance and Improved Power Factor - Chen, Jianbin; Yang, Chengyu; Zou, Jianjun; Chen, Kai (IEEE access, 2025)
Power factor correction (PFC) plays a crucial role in power electronics, particularly in enhancing the efficiency and stability of power systems. As continuous conduction mode (CCM) boost PFC converters become increasingly prevalent, research into their control strategies has deepened. While average current mode (ACM) control is commonly used, it faces several challenges in practical applications. Traditional ACM control methods struggle with input impedance regulation, especially within certain frequency ranges, where maintaining constant input impedance is difficult. This leads to issues such as current distortion and reduced efficiency. Additionally, bandwidth adjustment and ripple disturbance suppression with standard control procedures remain significant challenges. To address these issues, this paper proposes a novel multiplier-operated controller specifically designed for CCM boost PFC converters. The controller employs an innovative methodology to effectively modify and maintain input impedance at a defined constant within a specific frequency range. Furthermore, a specialized compensator is integrated to optimize bandwidth and minimize ripple disturbances. Experimental results from a 600W prototype demonstrate that the proposed controller achieves a power factor of up to 0.98 and significantly enhances efficiency and other performance metrics. This study provides new insights and technical approaches for improving the control strategies of CCM boost PFC converters.